Hydatid cyst submandibular gland, an unusal presentation: A case report - Manandhar, Sriti; Dhakal, S; Chettri, ST (Health Renaissance, 2017)
This is a case report of a sixteen years old female presented in the Otolaryngology and Head & Neck Surgery with left submandibular region which did not recovered by medical treatment. She underwent excision of left submandibular gland and hispathological examination confirmed the diagnosis as hydatid cyst of left submandibular gland. Health Renaissance 2015;13(3): 188-190